Dampak stres akademik dan cyberloafing terhadap kecanduan smartphone - Nacep Hamrat; Dede Rahmat Hidayat; Mohamad Syarif Sumantri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The purpose of this study was to investigate the effect of academic stress and cyberloafing to smartphone addiction. For this purposed, we conducted a survey from 225 participants of post-graduate student at Universitas Negeri Jakarta. This study was used Structural Equation Modelling (SEM) to evaluate the structural model. The result showed that stress academic positively significant affected both smartphone addiction and cyberloafing. The effect of cyberloafing positively significant on smartphone addiction. Stress academic and cyberloafing simultaneously had a positive significant effect to smartphone addiction.